An Autograph by Hasan Kafi Pruščak - Ljubović, Amir (Prilozi za orijentalnu filologiju, 2017)
The codex No 4579 (in the old inventory 23/59) in the Oriental Institute in Sarajevo is presented. In this codex there are two works written by Hasan Kafi Pruš:čak (full .name Hasan Kāfī b. Ṭurḫān b. Dāwūd b. Ya'qūb az-Zībī al-Aqḥiṣārī al-Bosnawi, born 1544, dead 1615 or 1616) in Arabic. He was one of the most distinguirshed Muslim intellectuals in Bosnia and Hercegovina under the Ottomans. His book The foundations of wisdom of the arrangement of the world (Uṣūl al-ḥikam fi niẓām al-'ālam) ,is translated into the French, Hungarian, German, Turkish and Serbo-Croatian. The author concludes, on the basis of elements provided by this codex, that the first document in this·codex with the title Nūr al-yaqīn fī uṣūl ad-dīn (pages 2b-52b), completed the 18th of ğumada I 1014 (the 1st October 1605) is the only autograph written by Hasan Kafi Pruščak that is found till now. The other writing in this codex is the work Ḥiadīqa aṣ-ṣalāt (pages 54b-95b) copied in writing by a certain Husayn in Gornji Vakuf in 1021. (1612). Two notes, wnitten by Hasan Kafi Pruščak, are presented too, the one only summarized and the other complete (the original and the translation). They are related to the battles fought for the conquest of Višegrad (Visegrad) and Ostmgon (Esztergom) in Hungary in which Hasan Kati took part himself. Because of all that, this codex is very important.